Análise da eficácia de um programa de intervenção na modificação da postura de protrusão de ombro por meio de exercícios para alteração de propriedades musculares - Diogo Barros de Moura Lima (2007)
Forward shoulder position (FSP) results from an altered scapula position on the rib cage. The scapular postural changes that potentially contribute to FSP are increases in medial rotation, lateral translation, superior translation and anterior tipping. FSP has a high prevalence and has been associated with dysfunctions and lesions of the upper quarter. Traditionally, FSP is considered as a result of force imbalance in scapulothoracic muscles (STM) where the anterior muscles are short and strong, and the posterior muscles are weak and long. However, the observed electromyographic silence of the STM in relaxed orthostatic posture, associated with the lack of association between active muscle force and posture, suggest that imbalance of passive forces of the STM, instead of active forces, could be responsible for the FSP. Considering that the passive force of a muscle is dependent on its stiffness and length, the objective of this study was to reduce the FSP in asymptomatic individuals, through alterations of these muscle characteristics, by performing hypertrophy training in specific lengths of the STM. Four studies using single-subject designs were carried out. Each study had three phases of six weeks duration: phase A was the baseline period, without intervention; intermediary phase, when the intervention started, but no changes in FSP were expected; and phase B, where the changes in FSP were expected with the maintenance of the intervention. Four asymptomatic individuals with FSP participated in this study. The dependent variables were weekly measures of scapula position and FSP during relaxed orthostatic posture. The measures were done by a movement analysis system. The independent variable was an intervention program planned to change the stiffness and length of the STM of each individual. This program was customized according to the participants needs, since the exercises were defined by the results of clinical assessments of stiffness and strength of the STM of each individual. The results were analyzed by visual analysis of graphics built from the time series data collected on the three phases, associated to appropriate statistical analysis for this type of design: two band standard deviation method (TB) e Repeated Measures ANOVA. Three out of four individuals presented increases in superior translation, anterior tipping of the scapula and in the measure of FSP. These increases happened, in most cases, in the intermediary phase. In addition, these changes happened bilaterally, even in the individual 1, who performed different exercises in each side of body, or in the individual 2, who exercised only one side. Thus, the pattern of use of the STM during occupational demands seems to be the main factor contributing to the observed changes instead of the exercises program. Therefore, interventions that do not modify the use pattern of the STM are, probably, not capable of reducing FSP.